Justice And Welfare - EN37 - 202301 - Berckholtz Benavides, Klaus (2023)
Normative economics and political philosophy are both concerned with the evaluation of social states and distributions: what constitutes a better economic distribution, or a fair way to sustain social and economic cooperation? How do the values of freedom, justice and welfare relate? The course centers around two broad families of approaches: those that focus on fairness or justice, and those that evaluate on the basis of welfare improvements. Topics to be considered include utility theory, economic efficiency, distributive justice and the morality of capitalism and socialism. The course is divided into four parts. Parts II and III are the most substantial parts, forming the backbone of the course. Part I: Rationality, Morality and Normative Economics Readings from Hausman & McPherson, Williams and supplementary materials provided by the instructor. Part II: Distributive Justice Readings from Hausman & McPherson, Williams, Rawls and Nozick as well as supplementary readings provided by the instructor. Part III: Markets and Socialism Readings from Cohen and Piketty as well as supplementary readings provided by the instructor. Part IV: Market Failure and Government Failure Supplementary readings provided by the instructor.